2016
DOI: 10.1177/1535370216662712
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: miR-194 inhibits proliferation and invasion and promotes apoptosis by targeting KDM5B in esophageal squamous cell carcinoma cells

Abstract: Increasing evidence suggests that miR-194 is down-regulated in esophageal squamous cell carcinoma tumor tissue. However, the role and underlying mechanism of miR-194 in esophageal squamous cell carcinoma have not been well defined. We used DIANA, TargetScan and miRanda to perform target prediction analysis and found KDM5B is a potential target of miR-194. Based on these findings, we speculated that miR-194 might play a role in esophageal squamous cell carcinoma development and progression by regulation the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…KDM5B, which belongs to the KDM5 family, can function as a transcriptional suppressor by specifically removing methyl residues from lysine 4 of histone 3 (H3K4), and consequently suppresses gene transcription [ 30 ]. A recently published study has shown that KDM5B exhibited tumorigenic activity in a variety of human cancer types [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…KDM5B, which belongs to the KDM5 family, can function as a transcriptional suppressor by specifically removing methyl residues from lysine 4 of histone 3 (H3K4), and consequently suppresses gene transcription [ 30 ]. A recently published study has shown that KDM5B exhibited tumorigenic activity in a variety of human cancer types [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been proposed that KDM5B is related to esophageal squamous cell carcinoma development via interactions with microRNA (miRNA). 12 miRNA upregulation suppresses papillary thyroid cancer development by a KDM5B-dependent manner. 13 The regulatory roles of miRNAs in gene expression in various human cancers have been adequately discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, a crucial role of histone lysine methylation in the epigenetic regulation of eukaryotic genes has been demonstrated, which suggested histone methylation disorders can cause cancer [21, 22]. KDM5B also involves in ESCA development and progression [23]. Here, a potential mechanistic association between the DNA methylation of KDM5B and the transcript levels of PSMB9 was proposed by Lamda3 , which provided a research clue to be tested further.…”
Section: Resultsmentioning
confidence: 88%